Morphology Control of Organic–Inorganic Bismuth‐Based Perovskites for Solar Cell Application. Issue 23 (10th September 2018) - Sanders, Simon; Stümmler, Dominik; Pfeiffer, Pascal; Ackermann, Nils; Schimkat, Florian; Simkus, Gintautas; Heuken, Michael; Baumann, Peter K.; Vescan, Andrei; Kalisch, Holger
Abstract : Recently, Pb‐based organometal halide perovskite solar cells have passed 20% power conversion efficiency (PCE). However, the main issue hampering commercialization is toxic Pb contained in these cells. Therefore, great attention is devoted to replace Pb by less harmful metals such as Bi. Yet, the most efficient methylammonium bismuth iodide (MBI) perovskite solar cells reported in literature reach PCE up to 0.2%. In this work, MBI perovskite solar cells, which are processed by spin‐coating under inert nitrogen atmosphere, employing a standard non‐inverted stack are presented. The control of perovskite morphology by modifying the process has been highlighted and the impact on photovoltaic (PV) characteristics has been shown. It is observed that the concentration of the perovskite solution (0.15–0.30 M) has a huge impact on the crystallite size, and the rotation speed during the spin‐coating process determines the layer coverage. Exposure of MBI solar cells to ambient air is found to be essential to obtain the highest short‐circuit current and open‐circuit voltage. The PCE increases over time, from 0.004% directly after processing up to 0.17% after 48 h. The fabricated cells exhibit an open‐circuit voltage of 0.72 V, which is the highest value published for this type of solar cell. Abstract : The morphology of spin‐coated methylammonium bismuth iodide (MBI) perovskites is investigated with a focus on performance for solar cell application. The crystallite size and coverage of the perovskite film are found to be adjustable by the concentration of the MBI solution and the rotation speed, obtaining open‐circuit voltages of 0.72 V and efficiencies of 0.17% in processed solar cells.